Additional Evidence for DDB2 T338M as a Genetic Risk Factor for Ocular Squamous Cell Carcinoma in Horses - Moriel H. Singer-Berk; Kelly E. Knickelbein; Zachary T. Lounsberry; Margo Crausaz; Savanna Vig; Nikhil Joshi; Monica Britton; Matthew L. Settles; Christopher M. Reilly; Ellison Bentley; Catherine Nunnery; Ann Dwyer; et al. (International Journal of Genomics)
Squamous cell carcinoma (SCC) is the most common periocular cancer in horses and the second most common tumor of the horse overall. A missense mutation in damage-specific DNA-binding protein 2 (DDB2, c.1012 C>T, p.Thr338Met) was previously found to be strongly associated with ocular SCC in Haflinger and Belgian horses, explaining 76% of cases across both breeds. To determine if this same variant in DDB2 contributes to risk for ocular SCC in the Arabian, Appaloosa, and Percheron breeds and to determine if the variant contributes to risk for oral or urogenital SCC, histologically confirmed SCC cases were genotyped for the DDB2 variant and associations were investigated. Horses with urogenital SCC that were heterozygous for the DDB2 risk allele were identified in the Appaloosa breed, but a significant association between the DDB2 variant and SCC occurring at any location in this breed was not detected. The risk allele was not identified in Arabians, and no Percherons were homozygous for the risk allele. High-throughput sequencing data from six Haflingers were analyzed to ascertain if any other variant from the previously associated 483 kb locus on ECA12 was more concordant with the SCC phenotype than the DDB2 variant. Sixty polymorphisms were prioritized for evaluation, and no other variant from this locus explained the genetic risk better than the DDB2 allele (P=3.39×10−17, n=118). These data provide further support of the DDB2 variant contributing to risk for ocular SCC, specifically in the Haflinger and Belgian breeds.